ANALISIS MANAJEMEN STRATEGI DAN SISTEM TANGGUNG RENTENG DALAM MENINGKATKAN SISTEM PENGENDALIAN INTERN DAN KINERJA KOPERASI DI PROVINSI JAWA TIMUR - Hadi, Mas Purnomo (Program Doktor Ilmu Ekonomi, 2008)
This research become of vital importance future specially to cooperation having saving and loan unit specially management of effort which use tanggung renteng system. Why this research become important because at least there is two reason of constitute that thing. The reason first, because this research will know giving of loan given by cooperation can give contribution to enable of family and improvement ability of member economic. The reason second is result of this research will become special reference of cooperation woman standardization in Province East Java in giving of credit or giving of loan to cooperation member with aim to make of prosperity of member through fund management of cooperation loan. Pursuant to fact is field and also research purposes and objectives hence special theory the used is theory of strategy management especially related to pattern of evolusioner applying of structure and strategy and also theory of strategy management concerning implementing business level strategies for the structure and control. Both of this theory include in theory of strategy management category concerning observation and structure. Method used to study this research use technique analyse modelling equation structural. Structural Equation Modelling (SEM) represent approach integrated between factor analysis, structural model and analysis of path. Technique analyse this can conduct examination of model for the structure of variable relation or for the development of new relation structure so that is finally obtained is newfangled. After conducted by gathering, processing and examination of data hence known result of research is overall of with result that business strategy variable have total influence equal to 0,623 to internal control system while variable of tanggung renteng system total influence to internal control system is 0,116. As according to conceptual framework is then known that internal control system have influence to cooperation performance equal to 0,939 mean internal control system have influence very significant to cooperation performance. This result at the same time indicate that research is real correct give result of meaning to continuity of cooperation future which is management of use system of tanggung renteng. So that this research give recommendation specially to financial, member commitment and controlling. Third of this indicator give big enough contribution to make of internal control system and cooperation performance. Key word : tanggung renteng and controlling